Efeito neuroprotetor da catequina sintética em modelo de depressão-símile por corticosterona em camundongos - Torres, Morgana Carla Souza (2023)
Depression is characterized as a recurrent and disabling mental disorder that affects more than 300 million people worldwide and has the following symptoms: depressed mood, anhedonia, tiredness, as well as cognitive, sleep or appetite disorders. The objective of the present study was to verify the anxiolytic, antidepressant and antioxidant effects of catechin (2R,3S)-2-(3,4-dihydroxyphenyl)-3,4-dihydro-2H-chromene-3,5,7-triol, a phenolic compound present in products of plant origin, in an animal model of depression induced by repeated administration of corticosterone (CORT). Adult female Swiss SPF (Specific Pathogen Free) mice were used (60 days), weighing between 19–28g, n= 80 (total animals) which received saline or corticosterone 20mg/kg (subcutaneously) for 21 consecutive days, and saline or catechin 10 mg/kg (intraperitoneally) from the 15th to the 21st day. On the 20th day, the animals were subjected to the perforated plate and elevated plus maze tests - LCE (anxious behavior). On the 21st day, they underwent open field tests (exploratory locomotor activity); tail suspension - SC and forced swimming - NF (depressive behavior). Then, the animals were euthanized, the brain areas collected (prefrontal cortex - PFC, striatum - CE and hippocampus - HC) to determine the levels of reaction to thiobarbituric acid (TBARS), reduced glutathione (GSH), nitrite and immunohistochemistry of cellular marker glial fibrillary acidic protein (GFAP) and inducible nitric oxide synthase (INOS). The results showed that corticosterone administration presented anxiety-like and depression-like behavior, as well as increased TBARS and nitrite levels, reduced GSH, and increased GFAP and INOS density. Treatment with catechin reversed the anxiogenic (LCE test) and depressive (NF test) effects. It also reversed the increase in TBARS levels in the CPF and HC, as well as the immunoreactivity of GFAP and INOS in the CPF. In conclusion, the results demonstrated that catechin had an anxiolytic and antidepressant effect in behavioral tests induced by CORT, which seem to be related to the antioxidant, neuroinflammatory action and protection of synaptic defects induced by CORT.